Fusion-Activated Ca(2+) Entry: An “Active Zone” of Elevated Ca(2+) during the Postfusion Stage of Lamellar Body Exocytosis in Rat Type II Pneumocytes - Miklavc, Pika (Public Library of Science, 2010)
BACKGROUND: Ca(2+) is essential for vesicle fusion with the plasma membrane in virtually all types of regulated exocytoses. However, in contrast to the well-known effects of a high cytoplasmic Ca(2+) concentration ([Ca(2+)](c)) in the prefusion phase, the occurrence and significance of Ca(2+) signals in the postfusion phase have not been described before. METHODOLOGY/PRINCIPAL FINDINGS: We studied isolated rat alveolar type II cells using previously developed imaging techniques. These cells release pulmonary surfactant, a complex of lipids and proteins, from secretory vesicles (lamellar bodies) in an exceptionally slow, Ca(2+)- and actin-dependent process. Measurements of fusion pore formation by darkfield scattered light intensity decrease or FM 1-43 fluorescence intensity increase were combined with analysis of [Ca(2+)](c) by ratiometric Fura-2 or Fluo-4 fluorescence measurements. We found that the majority of single lamellar body fusion events were followed by a transient (t(1/2) of decay = 3.2 s) rise of localized [Ca(2+)](c) originating at the site of lamellar body fusion. [Ca(2+)](c) increase followed with a delay of ∼0.2–0.5 s (method-dependent) and in the majority of cases this signal propagated throughout the cell (at ∼10 µm/s). Removal of Ca(2+) from, or addition of Ni(2+) to the extracellular solution, strongly inhibited these [Ca(2+)](c) transients, whereas Ca(2+) store depletion with thapsigargin had no effect. Actin-GFP fluorescence around fused LBs increased several seconds after the rise of [Ca(2+)](c). Both effects were reduced by the non-specific Ca(2+) channel blocker SKF96365. CONCLUSIONS/SIGNIFICANCE: Fusion-activated Ca(2+) entry (FACE) is a new mechanism that leads to [Ca(2+)](c) transients at the site of vesicle fusion. Substantial evidence from this and previous studies indicates that fusion-activated Ca(2+) entry enhances localized surfactant release from type II cells, but it may also play a role for compensatory endocytosis and other cellular functions.